MESEUM GENTALA ARASY SEBAGAI SUMBER BELAJAR SEJARAH ISLAM DI JAMBI - Oktafiany, Dea; Pamungkas, Satriyo (Universitas Batanghari Jambi, 2022)
The purpose of this research is to find out the collection of objects in the Gentala Arasy Museum and explain the use of the Gentala Arasy museum in learning Islamic history in Jambi. The research method that will be used to examine the Gentala Arasy Museum as a source of learning Islamic history in Jambi is a qualitative descriptive method. The results of the study provide an illustration that the Gentala Arasy museum has collections of relics from Islamic culture in Jambi City. These objects were obtained from various areas of Jambi by replacing them or donated by their owners to be used as museum collections. The process of learning history at SMK N 4 Jambi City, teachers use more lecture and question and answer methods where students are invited to dialogue with teachers about the material being taught without students understanding the object being studied. In addition to the method, in learning history also requires a variety of media. In the subject of the development of Islam in the archipelago and its heritage, the material is related to the development of Islam in Jambi by way of students visiting the Museum to study the various collections of objects that exist. From the results of student questionnaires about the feasibility of the Gentala Arasy museum as a learning resource, it can be categorized as high an average of 77.14% of students stating that the Gentala Arasy museum is worthy of being a source of learning history.